URGENSI KOMPENSASI TERHADAP MOTIVASI GURU (Perspektif Desentralisasi Pendidikan) - Mukaffan, Mukaffan (JURNAL TADRIS STAIN PAMEKASAN, 2010)
Abstract: Compensation in education is everything accepted by educators or employees such as fringe, benefits, or  rewards for their works in order to improve their professionalism, motivation and job satisfaction and necessities. Compensation can include money, benefits, additional wages, gifts, health insurance, vacation, and so forth. The problem is on the compensation disparity between educators or employees who are civil servants and temporary, whether they are  in domestic institutions or in the private sector, which in turn,  affects  the quality of education. Compensation improvements should be continually arisen to improve teacher motivation.